Long Non-coding RNA H19 Augments Hypoxia/Reoxygenation-Induced Renal Tubular Epithelial Cell Apoptosis and Injury by the miR-130a/BCL2L11 Pathway - Yuan, Yuan; Li, Xiaoling; Chu, Yudong; Ye, Gongjie; Yang, Lei; Dong, Zhouzhou (Frontiers in Physiology, 2021)
Acute kidney injury (AKI) is a severe kidney disease defined by partial or abrupt loss of renal function. Emerging evidence indicates that non-coding RNAs (ncRNAs), particularly long non-coding RNAs (lncRNAs), function as essential regulators in AKI development. Here we aimed to explore the underlying molecular mechanism of the lncRNA H19/miR-130a axis for the regulation of inflammation, proliferation, and apoptosis in kidney epithelial cells. Human renal proximal tubular cells (HK-2) were induced by hypoxia/reoxygenation to replicate the AKI model in vitro. After treatment, the effects of LncRNA H19 and miR-130a on proliferation and apoptosis of HK-2 cells were investigated by CCK-8 and flow cytometry. Meanwhile, the expressions of LncRNA H19, miR-130a, and inflammatory cytokines were detected by qRT-PCR, western blot, and ELISA assays. The results showed that downregulation of LncRNA H19 could promote cell proliferation, inhibit cell apoptosis, and suppress multiple inflammatory cytokine expressions in HK-2 cells by modulating the miR-130a/BCL2L11 pathway. Taken together, our findings indicated that LncRNA H19 and miR-130a might represent novel therapeutic targets and early diagnostic biomarkers for the treatment of AKI.